Modelling of soot formation in a diesel engine with the moment projection method. (December 2017) - Wu, Shaohua; Yapp, Edward K.Y.; Akroyd, Jethro; Mosbach, Sebastian; Xu, Rong; Yang, Wenming; Kraft, Markus
Abstract: In this work, the recently developed moment projection method (MPM) is coupled with the Stochastic Reactor Model engine code to simulate the formation of soot in a direct injection diesel engine. The simulations take into account convective heat transfer, turbulent mixing, and adopts a detailed chemical mechanism so that the concentrations of soot precursors can be predicted. The soot model considered in this work is based on integration and modification of existing sub-models for soot inception, coagulation, condensation, surface growth and oxidation. The soot moment equations are solved using MPM which has been proven to be accurate and robust. A single-cylinder research version of the Great Wall 4D20 diesel engine with exhaust gas recirculation is modelled for two test cases with different injection timings, injection pressures and fuel consumptions. Simulations are fast (on the order of minutes) and comparison of computed and experimental pressure and heat release rate are in excellent agreement. The amount of soot produced is in qualitative agreement with measurements of diesel smoke opacity.